Adaptive and Passage-Based Fault-Tolerant Routing Methods for Three-Dimensional Mesh NoCs - Yota Kurokawa; Masaru Fukushi (Chips, 2025)
This paper proposes novel two fault-tolerant routing methods for a 3D mesh network-on-chip (NoC). The existing method proposed by Boppana et al. combines two routing methods, minimal fully adaptive routing and fault-tolerant routing, for faulty region detouring. However, in the latter fault-tolerant routing, a detour direction is statically defined for each faulty region. Due to the long detour path and the use of eight virtual channels, this method has the problems of high communication latency and a large hardware overhead. To solve these problems, the first proposed method allows adaptive detours for faulty regions, and the second proposed method allows the passage of them. The simulation results show that, compared with the existing method, the second proposed method enables us to reduce the latency by about 30% and improve the throughput by about 3.1% with half of the virtual channels.